Femoroperoneal bypass: evaluation of potential for revascularization of the severely ischemic lower extremity. - Reichle, F A (1975)
In 79 patients in whom distal small vessel bypass with autogenous vein was used for revascularization because of gangrene, gangrenous ulceration or rest pain, 14 had femoroperoneal bypasses. Femorotibial or femoroperoneal bypasses were performed in those patients in whom no popliteal runoff was present on pre-operative arteriogram. Femoroperoneal bypass was performed in preference to primary amputation in each case. Nine of 14 (64.3%) of femoroperoneal bypasses were functional whereas 57 of 79 (72.2%) of total distal bypasses to small vessels were functional. Salvage of severely ischemic lower extremities was achieved in 5 of 14 (35.7%) patients after femoroperoneal bypass and in 46 of 65 (70.8%) patients after bypass to anterior tibial or posterior tibial arteries. Graft patency without limb salvage occurred in 4 of 9 (44.4%) patients with patent femoroperoneal bypasses and in only 2 of 48 (4.2%) of patients with femorotibial bypass. Although limb salvage rate is considerably less with femoroperoneal than femorotibial or femoropopliteal bypass, attempted limb revascularization by peroneal bypasses is preferable to primary amputation in patients with rest pain, gangrenous ulceration or gangrene.